Analisis Penjadwalan Pembangunan Tangki di PT ABC Menggunakan Critical Path Method (CPM) dan Program Evaluation and Review Technique (PERT) - Septiana Alia Pratiwi; Misrianto Misrianto; Alip Fandika; Dutha Ramadhan (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Project Management played an important role in determining to succussed a project. The Tank construction project carried out by PT. ABC encountered obstacles namely the project was completed later than scheduling planned therefore had an impact higher cost. This study aims to optimize the scheduling of tank construction by PT ABC. The sample in this study is an XYZ Project in construction tank. This study uses the critical path method (CPM) and Program Evaluation and Review Technique (PERT) approaches. The results show that there are 18 activities (form A-R as symbolic) in the XYZ Project for construction tank over 87 days as planned. Implementation CPM with forward and backward method project completed around 66 days. Otherwise, PERT analysis used forward and backward method project completed around 67,5 days or 21,5 faster than planned. Therefore, it can be concluded that the both of methods had a gap 1 working days that distributed in 12 work activities namely A, B, C, E, F, G, M, N, O, P, Q, R. Keywords : CPM, Optimization, PERT, Project Management, Scheduling.